PROTOTIPE PEMANTAU GAS HIDROGEN SULFIDA (H2S) DALAM RUANG INDUSTRI KIMIA - , ZIYAURROHMAN ALLADANY ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Prototype gas monitoring hydrogen sulfide (H2S) in the chemical industry is a prototype suitable used in industries related to dangerous chemicals. In an industry that thriving now is not all gas industries using tools to monitor when there is exposure to hazardous gases. To avoid of occurrence of a disservice and hazardous then one of his steps namely by making tools to monitor where gas h2s Prototype this will resembling a miniature room square-shaped as a room industry that there is a hazardous chemicals that can leak or bursting time. Besides furnished with a panel that was an LCD, the buzzer for alarm. Indicators LED as a sign, and fan as neutralizing air. So that circulation indoor air into clean again in line with the standard determined. As a control of LCD, buzzer, alarm, LED and exhaust fan the equipment uses a system minimum and a sensor as input. The unit of measurement gas to know the quality of the air is ppm (part per million).